A review on oral tactile sensitivity: measurement techniques, influencing factors and its relation to food perception and preference. (September 2022) - Liu, Jing; Cattaneo, Camilla; Papavasileiou, Maria; Methven, Lisa; Bredie, Wender L.P.
Highlights: The review concentrated on several aspects of oral tactile sensitivity. Methods in measuring oral tactile sensitivity including their advantages and disadvantages were reviewed. The review elaborated factors that influenced oral tactile sensitivity. The association between oral tactile sensitivity and texture perception/preference was discussed. Abstract: Texture perception and mouthfeel are important factors in food acceptance and rejection. Despite the contribution of oral tactile sensation to perception of food texture, it has been understudied. This review addresses oral tactile sensitivity in relation to measurement methods, factors that influence sensitivity, and its association with texture perception and preference. Notably, the advantages and disadvantages of different testing methods are discussed, including the two-point discrimination task (or two-pin test), the grating orientation test, the letter-identification test, point pressure sensitivity by filaments, and discrimination tests for specific aspects of texture. The effects of age, sex, fungiform papillae, ethnicity, pathological changes and other physiological measures on oral tactile sensitivity are also reviewed. The oral tactile sensitivity tends to decline with advanced age in healthy adults; some pathological changes may have negative influence on the tactile sensitivity; however, the effect of several other factors are contradictory in the literature. Regarding the association between oral tactile sensitivity and texture perception and food preferences, it is suggested that the sensitivity measured by techniques such as the two-point discrimination task or a grating orientation task typically represents a single dimension of texture perception and thus is difficult to link directly to perception of other texture dimensions. The sensitivity to specific texture attributes such as thickness might predict texture perception and preference. The review stresses the importance of further research in oral tactile sensitivity and its role in the perception and liking of various food textures.